2019
DOI: 10.1080/13603116.2019.1698064
|View full text |Cite
|
Sign up to set email alerts
|

Standing alone: sexual minority status and victimisation in a rural lower secondary school

Abstract: Studies worldwide indicate that sexual minority students often face different forms of bullying in everyday life at school, and young people growing up in communities with conservative values, such as in rural areas, are often in a particularly vulnerable position. Nonetheless, there is an absence of studies addressing the everyday lives of sexual minority students in rural schools. Drawing on interviews with students in the ninth grade of a rural lower secondary school in Sweden, the current study has investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…I have not analysed these aspects, but in my research I found out that locality and social class are meaningful aspects (see Lehtonen, 2018). Youth living in rural areas were more likely than those living in cities to both hide their sexuality and gender from other students and their teachers at school, but they also faced negative reactions to their sexuality and gender identity more often than respondents living in cities (see also Odenbring, 2019). Respondents with working-class backgrounds faced violence more often than those with middle-class backgrounds.…”
Section: School As Context Of Heteronormative Violencementioning
confidence: 96%
See 1 more Smart Citation
“…I have not analysed these aspects, but in my research I found out that locality and social class are meaningful aspects (see Lehtonen, 2018). Youth living in rural areas were more likely than those living in cities to both hide their sexuality and gender from other students and their teachers at school, but they also faced negative reactions to their sexuality and gender identity more often than respondents living in cities (see also Odenbring, 2019). Respondents with working-class backgrounds faced violence more often than those with middle-class backgrounds.…”
Section: School As Context Of Heteronormative Violencementioning
confidence: 96%
“…I have analysed it as a central way to construct proper heteronormative masculinities for boys in school context. In my earlier research, I found that youth reported that "sometimes homophobic name-calling was not targeted towards known gay people while they might get insulted, and it was only used between straight boys" (see Pascoe, 2007;Odenbring, 2019). But of course, especially for LGBTI youth, hearing negative homophobic reactions and name-calling creates an unpleasant atmosphere, even if they are not the direct targets.…”
Section: School As Context Of Heteronormative Violencementioning
confidence: 99%
“…For example, intimate partner violence in Sweden remains high compared to other European countries ( Gracia and Merlo, 2016 ), and the MeToo movement showed the pervasiveness of sexual violence and harassment in Sweden. Besides, studies show that alongside the ‘openness’, ‘traditional’ sexual scripts and strong heteronormative values coexist in Swedish society ( Linander et al., 2021 ; Odenbring, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homophobia [23,24] It is the rejection, discrimination and/or constant hatred of heterosexual people towards homosexual people or belonging to the LGTBI+ community due to their sexual orientation and/or gender identity.…”
Section: Types Of School Bullying Boosters Definitionmentioning
confidence: 99%